Comparison of Infant Vitamin D Supplement Use Among Canadian-Born, Immigrant, and Refugee Mothers. (May 2015) - Moffat, Tina; Sellen, Daniel; Wilson, Warren; Anderson, Laura; Chadwick, Sarah; Amarra, Sofia
Purpose: This study compares knowledge and practice of infant vitamin D supplementation among immigrant, refugee, and Canadian-born mothers.Method: Focus group discussions with 94 mothers of children aged 0 to 3 years recruited from early childhood centers and a refugee health clinic.Findings: Both immigrant and Canadian-born mothers indicated good knowledge and use of infant vitamin D supplementation. In contrast, Canadian government-assisted refugees were less likely to supplement with vitamin D. The main source of information about vitamin D was public health prenatal classes. Many mothers reported inconsistent guidance from health care providers.Discussion and Conclusions: Exclusively breastfed infants of refugees may be more at risk of vitamin D deficiency. All mothers require clear recommendations, both in clinical and public health settings.Implications for Practice: Mothers, both new Canadian and Canadian-born, require clear and consistent messaging from health professionals. Refugee mothers, however, require more educational support to promote infant vitamin D supplementation.